Study of ventilator-associated tracheobronchitis in respiratory ICU patients and the impact of aerosolized antibiotics on their outcome - Hanaa Ali (The Egyptian Journal of Bronchology, 2016)
Abstract Background Lower respiratory tract infections in intubated patients include ventilator-associated tracheobronchitis (VAT) and ventilator-associated pneumonia. Aerosol delivery to intubated patients has improved with advances in techniques and with the development of newer aerosol generators. Aim The aim of the current study was to assess VAT and study the effect of aerosolized antibiotics (AAs) as an adjuvant to systemic antibiotic (SA) on outcome in VAT patients over 18 months, starting from December 2013, who were admitted to the respiratory ICU of Ain Shams University Hospital. Patients and methods Seventy-four patients out of 104 mechanically ventilated patients admitted to the respiratory ICU were subjected to serial mini-BAL sputum sampling from the first day of mechanical ventilation (MV). Thirty-two patients who developed VAT were divided into two groups: group I (13 VAT patients who received AAs in the form of ceftazidime 500 mg/12 h+amikacin 400 mg/12 h added to the SA) and group II (10 VAT patients who received only SA). The current study included only those patients whose relatives agreed to share in the study. All patients were subjected to daily assessment for signs of respiratory tract infection and to twice weekly chest radiography, leukocytic count evaluation, and microbiological assessment using mini-BAL. Results VAT incidence was found to be 22.1%. Eighty percent of patients who received AAs showed clinical improvement in the form of significant decrease in temperature, amount of sputum, and leukocytic count, and significant increase in PaO2/FiO2 ratio, in comparison with 30% in the SA group. Conclusion The incidence of VAT was found to be 22.1%, and was mainly caused by Gram-negative bacteria. AAs adjuvant to SA were effective in rapid resolution of signs of respiratory infection, in causing decreased bacterial load, reduced bacterial resistance, reduced progression of VAT to ventilator-associated pneumonia, reduced days of SA use, decreasedMVdays and ICU stay days, and probably reduced cost of ICU admission, but did not affect mortality.